Pengaruh Budaya Kerja, Kompensasi dan Etos Kerja Terhadap Kinerja Karyawan Pada PT. Telkom Mamuju - Nur Jaya Baiduri Ruslan; Ira Nasriani; Irma Irma; Andi Kamal M.Sallo; Nur Afra; Ahmad Zulfiqram (CV. Ulil Albab Corp, 2024)
This research aims to examine the influence of work culture, compensation and work ethic on employee performance at PT. Telkom Mamuju. The data in this research was obtained from each employee at PT. Telkom Mamuju is willing to be a respondent. This research uses primary data by conducting direct research in the field by giving questionnaires/question sheets to 57 respondents. The data analysis method used is multiple linear regression analysis. The research results show that: partially, the variables of work culture, compensation and work ethic have a positive and significant effect on employee performance.